A bridge to surgery for obstructive colorectal cancer - Morita, Shunji (Annals of Laparoscopic and Endoscopic Surgery, 2019)
Colorectal cancer can present as an emergency, with bowel obstruction, perforation, and bleeding, requiring urgent surgical intervention. Bowel obstruction was reported to be seen in 15–20% of patients with colorectal cancers (1,2). The treatment for obstructive colorectal cancer (OCRC) has been of great interest to colorectal surgeons because of poor surgical outcomes.